Differences in Urinary Bacterial Anti-Adhesion Activity after Intake of Cranberry Dietary Supplements with Soluble versus Insoluble Proanthocyanidins. (3rd September 2022) - Howell, Amy B.; Dreyfus, Jean-François; Chughtai, Bilal
Abstract: A number of clinical trials support the use of standardized cranberry supplement products for prevention of urinary tract infections; however, products that are not well-characterized for sufficient levels of bioactive components may contribute to negative clinical outcomes. Cranberry supplements for consumer use are not regulated and can be formulated different ways using cranberry juice, pomace or various combinations. This can lead to consumer confusion regarding effectiveness of individual products. The current study compared two commercial supplement products, one made from cranberry juice extract and the other from a blend of whole cranberry. The influence of formulation and proanthocyanidin (PAC) solubility on in vitro and ex vivo P-fimbriated Escherichia coli bacterial anti-adhesion activity (AAA) was determined. Both supplement products as well as whole, frozen cranberries were chromatographically separated into crude polyphenolic, sugar and acid fractions. In vitro AAA testing of all fractions confirmed that only those containing soluble PACs elicited activity. The cranberry juice extract product had higher soluble PAC content than the whole cranberry blended product, which contained mainly insoluble PACs. The influence of soluble and insoluble PAC levels in each product on the urinary (ex vivo) AAA was determined following ingestion. The juice extract product was associated with significantly higher urinary AAA than that of the whole berry blended product when consumed once daily over the 1-week intervention period.